Implicit Simulation for Three-Dimensional Spatial Morphology of Geological Body Based on Marching Cubes Algorithm - Ding, Ming Lei; Zou, Yan Hong; He, Jian Chun (Applied Mechanics and Materials, 2012)
Due to the discrete and incomplete sample data for the geological body in geological investigation, it is difficult to construct the three-dimensional model of geological body. Therefore, based on data interpolation, we propose a method to implement the three-dimensional implicit simulation for the geological body by programming with marching cubes algorithm. Firstly, the spatial interpolation method is used to predict the distribution trend of geological body and the three-dimensional spatial regular data field for the geological body is established. Secondly, the three-dimensional isosurface of geological body is extracted from discrete points by the marching cubes algorithm. Finally, combining with three-dimensional visualization technology of OpenGL, three-dimensional spatial morphology of geological body is simulated by tiny triangle approximation in computer graphics. Taken the borehole data in exploration engineering as example, this method is applied to develop the three-dimensional implicit simulation for ore body. The result of implicit simulation is close to the delineation of explicit simulation by human-computer interaction in three-dimensional geological modeling software. It shows that this method is feasible and efficient for the three-dimensional simulation of geological body.